Innovation in the classroom: Engaging English as a foreign learning students using project-based learning - Alif Karyawati; Ashadi Ashadi (LingTera, 2018)
Project based learning (PBL) is an instructional approach that focuses on student centre learning, learning process, and students’ autonomy. This study was conducted at International Class Program in one of universities in Salatiga. Furthermore, this study explained the teaching strategies by using project based learning in English drama class. The researcher used a case study as the design and collected the data by using interview and observation. The participants of this study were an English drama lecturer and 20 students of International Class Program (ICP). The findings indicate that ICP students dominated the class especially to improve their speaking skill and the lecturer provided new learning atmosphere in teaching English by giving some activities which contains communication, critical thinking, collaboration, and creativity or 4Cs skills.